2017
DOI: 10.5539/jfr.v6n2p75
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Probiotic Bacteria during Refrigerated Storage of Commercial Probiotic Fermented Dairy Products Marketed In Jordan

Abstract: Objectives: The study aimed to measure the viability of probiotic bacteria in different probiotic fermented dairy products marketed in Jordan during their shelf lives. Methods:Ten products which were all known commercial probiotic fermented dairy drinks were purchased from main market stores at 0 day of processing, and kept under 4 o C for the assigned time intervals (1, 7, 14 day). These products included 7 stirred yogurt Activia, Activia low-fat, Actimel, Baladna, Acti-Yogho, Moffedo, and Vital, and 2 set yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Although, it didn't significantly differs from D3 (free-fat drink with 1% oat) and D 2 (low-fat drink with 2% oat) which have TA% numbers of 1.93 and 1.87%, respectively. These results are in accordance with Sayed (2012), Coman et al (2013), Abou-Dobara et al (2016) and Haddad (2017).…”
Section: • the Ph Values And Titratable Aciditysupporting
confidence: 92%
“…Although, it didn't significantly differs from D3 (free-fat drink with 1% oat) and D 2 (low-fat drink with 2% oat) which have TA% numbers of 1.93 and 1.87%, respectively. These results are in accordance with Sayed (2012), Coman et al (2013), Abou-Dobara et al (2016) and Haddad (2017).…”
Section: • the Ph Values And Titratable Aciditysupporting
confidence: 92%
“…The viability of probiotics during storage is strain or species-dependent, and it is also influenced by the manufacturing process or composition of probiotic products. Most of the studies showed that the survival of probiotics could be steadily maintained in the commercial products over the storage duration, although some probiotics might slightly lose their viability (Shah et al 2000;Al-Otaibi 2009;Liu 2011;Dharmasena 2012;Haddad 2017;Sumalapao et al 2017). However, the viability of the opened commercial cultured probiotic milk and their physicochemical properties, especially pH and D-lactic acid, are yet to be examined after being opened and stored for a few days.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the importance of similar compounds is now recognized when speaking of hygienic issues and different therapies for human illnesses (114)(115)(116)(117)(118)(119), and other arguments (120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133).…”
Section: Discussionmentioning
confidence: 99%